2018
DOI: 10.1016/j.ydbio.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of the house secreting epithelium, a major innovation of tunicate larvaceans, involves multiple homeodomain transcription factors

Abstract: The mechanisms driving innovations that distinguish large taxons are poorly known and essentially accessible via a candidate gene approach. A spectacular acquisition by tunicate larvaceans is the house, a complex extracellular filtration device. Its components are secreted by the oikoplastic epithelium which covers the animal trunk. Here we describe the development of this epithelium in larvae through the formation of specific cellular territories known to produce distinct sets of house proteins (Oikosins). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The OE cell specification may occur depending on the cell position around hatching or later stages after the OE precursor cells are spatially arranged bilaterally (Kishi et al., 2017). In accordance with this notion, several homeobox transcription factor genes show distinct expression in hatched larva before OE specification (Mikhaeva et al., 2018). RNAi‐mediated knockdown of propA or propB caused a reduction of some dorsal midline cells, and abrogated the region‐specific oikosin41 expression (Mikhaeva et al., 2018).…”
Section: Imagingmentioning
confidence: 71%
See 1 more Smart Citation
“…The OE cell specification may occur depending on the cell position around hatching or later stages after the OE precursor cells are spatially arranged bilaterally (Kishi et al., 2017). In accordance with this notion, several homeobox transcription factor genes show distinct expression in hatched larva before OE specification (Mikhaeva et al., 2018). RNAi‐mediated knockdown of propA or propB caused a reduction of some dorsal midline cells, and abrogated the region‐specific oikosin41 expression (Mikhaeva et al., 2018).…”
Section: Imagingmentioning
confidence: 71%
“…In accordance with this notion, several homeobox transcription factor genes show distinct expression in hatched larva before OE specification (Mikhaeva et al., 2018). RNAi‐mediated knockdown of propA or propB caused a reduction of some dorsal midline cells, and abrogated the region‐specific oikosin41 expression (Mikhaeva et al., 2018).…”
Section: Imagingmentioning
confidence: 71%
“…However, the authors showed that the regional specific expression of the oikosins in the oikoplastic epithelium corresponds to spatially restricted presence of the corresponding oikosins in the house. Mikhaleva et al (2018) showed that the expression of the approximately 80 known variants of oikosin genes in O . dioica is developmentally controlled by hox genes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the loss of muscles to propel fluid inside the organism could be considered the result of regressive evolution during the transition from a sessile filter-feeding ascidian-like strategy, in which contraction of siphon muscles is responsible for water current, to a pelagic filter-feeding strategy based on the innovation of the appendicularian house, in which water circulation is mostly propelled by tail beating 68 . Considering that in addition of tail beating, water circulation is also propelled by fined tuned movement of the cilia in the gills that can efficiently reverse the direction of the water flow, inwards during feeding or outwards during the inflation of the house, it is also plausible to think that instead of being a process of regressive evolution, the loss of In conclusion, our results support an evolutionary adaptive scenario in which the deconstruction of cardiopharyngeal GRN could have contributed to the loss of features that characterize ascidianlike sessile lifestyle, and the acquisition of novel features that enabled its transition to a pelagic free-living active style connected to the innovation of the house (Fig.…”
Section: Evolution Of Pelagic Appendicularians From a Sessile Ascidiamentioning
confidence: 99%